SPE Production and Operations Symposium 2009
DOI: 10.2118/119639-ms
|View full text |Cite
|
Sign up to set email alerts
|

Novel Perforating Job Design Triples Well Productivity

Abstract: Well productivity is driven by establishing a clean connection through the near wellbore zone of drilling and completion induced permeability impairment commonly referred to as the "near wellbore damaged zone". This connection through the damaged zone is most often achieved by perforating with explosive shaped charges. The effectiveness of this connection is the result of perforator selection criteria and the well environment in which the perforating job is executed. In the depleted oil field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Lee and Sidle (2010) showed that values of b equal to or greater than unity can cause the reserves to have physically unreasonable properties. To avoid this drawback, "stretched-exponential" models have been proposed recently (Valkó 2009;Ilk et al 2008Ilk et al , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Lee and Sidle (2010) showed that values of b equal to or greater than unity can cause the reserves to have physically unreasonable properties. To avoid this drawback, "stretched-exponential" models have been proposed recently (Valkó 2009;Ilk et al 2008Ilk et al , 2009.…”
Section: Introductionmentioning
confidence: 99%